PENINGKATAN LITERASI MATEMATIS PESERTA DIDIK SMP NEGERI 5 SERUWAY MELALUI MODEL PEMBELAJARAN MISSOURI MATHEMATICS PROJECT (MMP) - Rina Andreyanti; Saiman Saiman (Universitas Islam Nusantara, 2023)
Research. It's purposeful. to be able to know. the existence of increasing the mathematical literacy of students in grades VII-1 of SMP Negeri 5 Seruway after experiencing learning using the Missouri Mathematics Project (MMP) learning model. The design in this study One-Group Pretest-Posttest Design. The research sample used was students in grades VII-1 of junior high school. Land 5 Seruway. The technique.. used to collect data, namely pre-test and post-test.Based on the results of hypothesis testing, =2,048 and =36.7 were obtained, so that (36.7 2,048) with a significant level of 5% so that not rejected and rejected, this means that there is an increase in the mathematical literacy of students after experiencing learning using the MMP learning model at SMP Negeri 5 Seruway.